KOMUNIKASI NON VERBAL DALAM AL-QUR’AN - Rahmadianawati (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to analyze the concept of non-verbal communication in the Qur'an, the concept of non-verbal communication in the perspective of communication experts, as well as the relationship between the concept of non-verbal communication in the Qur'an and the concept of non-verbal communication in the perspective of communication science experts. This study uses a naturalistic qualitative approach and is descriptive analytic because the data to be examined is data that illustrates complex and concrete social reality. Then it can be concluded that the gesture, body language, facial expressions and eye contact everyone who plays a role in the process of non -verbal communication that is related to this research can be used as a source of data. The data collection was carried out with an instrumental observation. In-depth interviews and study of documents relating to non-verbal communication theory in the Qur'an. The results showed that the concept of non-verbal communication in the Qur'an is the process of delivering communication that does not use words, but in the form of smiles, crying and behavior